2012
DOI: 10.1108/00012531211244815
|View full text |Cite
|
Sign up to set email alerts
|

How do health care professionals select medical images they need?

Abstract: PurposeThis paper aims to report the results of a study investigating the relevance criteria used by health care professionals when seeking medical images.Design/methodology/approachData were collected from 29 participants using a think‐aloud protocol and face‐to‐face interviews and analysed using the Straussian version of grounded theory (GT).FindingsThe results show that participants made use of 15 relevance criteria, although they agreed on topicality being the most important. The findings suggest that user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Healthcare professionals determine relevance through a combination of textual background information, visual inspection, and mental comparison to imagined ideals (Sedghi, Sanderson, & Clough, 2012). Personal experience trumps other criteria, however, when determining image relevance (Markonis et al, 2012;Müller et al, 2006).…”
Section: Biomedicinementioning
confidence: 99%
“…Healthcare professionals determine relevance through a combination of textual background information, visual inspection, and mental comparison to imagined ideals (Sedghi, Sanderson, & Clough, 2012). Personal experience trumps other criteria, however, when determining image relevance (Markonis et al, 2012;Müller et al, 2006).…”
Section: Biomedicinementioning
confidence: 99%
“…And intensity of the light is nothing but the Value. These three dimensional representation with the use of HSV color space is termed as a hexacone, and intensity is represented by the central vertical axis [9]. Hue is defined as an angle in the range [0,2π] relative to the Red axis with red at angle 0, green at 2π/3, blue at 4π/3 and red again at 2π.…”
Section: Figure 1 Hsv Planes Of Color Imagementioning
confidence: 99%
“…The question of image similarity has important applications in the medical domain because diagnostic decision-making has traditionally involved using evidence from a patient's data (image and non image) coupled with the physician's prior experiences of similar cases [8]. A recent study [9] has shown that manual selection of these similar cases is primarily based upon visual properties. It has been suggested that the reliance on imaging for various clinical workflows means that access to relevant stored data will allow for more informed and effective treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical environments, the selection of similar studies is primarily based upon topicality, i.e., whether or not the images contain the same subject matter; judging whether a study is topical is primarily decided upon using the visual characteristics of the images [15]. However, the search capabilities provided by PACS are based on textual keywords, such as patient names, identifiers, and image device.…”
Section: Motivationmentioning
confidence: 99%